Co‐creating youth justice practice with young people: Tackling power dynamics and enabling transformative action - Smithson, Hannah; Jones, Anna (Children & society, 2021)
This paper provides an account of an innovative research project that enabled the co‐creation with justice‐involved young people of a transformative framework of practice, termed Participatory Youth Practice (PYP). We present a description of our participatory research processes and reflect on our attempts to rebalance inherent power dynamics when working with marginalised young people. We demonstrate how young people's meaningful participation in research can strengthen their participation in service design and delivery. The embedding of the PYP framework in youth justice practice across a large region in England is a formative step in understanding the importance of young people's participation.